June’s Grace in the Hills - Rolla Clymer (Symphony in the Flint Hills, 2014)
The Month of Many Rains has ministered bounteously to the Kansas Flint Hills as they awakened from their long sleep; the dainty Month of Many Flowers has adorned them with her magic. Now comes June–the Month of Rare Delight–and crowns them with her mature and stately beauty.
Keywords: prose; story; poem; beauty; June; months; nature; flowers; grass; Flint Hills; Kansas; silence; serenity; marvelous; land; Nature